The efficiency of universal mitochondrial DNA barcodes for species discrimination of Pomacea canaliculata and Pomacea maculata - Kannan, A.; Suganiya, R. R.; Ratnayeke, Shyamala *; Yow, Yoon Yen * (2020)
Invasive apple snails, Pomacea canaliculata and P. maculata, have a widespread distribution globally and are regarded as devastating pests of agricultural wetlands. The two species are morphologically similar, which hinders species identification via morphological approaches and species-specific management efforts. Advances in molecular genetics may contribute effective diagnostic tools to potentially resolve morphological ambiguity. DNA barcoding has revolutionized the field of taxonomy by providing an alternative, simple approach for species discrimination, where short sections of DNA, the cytochrome c oxidase subunit I (COI) gene in particular, are used as ‘barcodes’ to delineate species boundaries. In our study, we aimed to assess the effectiveness of two mitochondrial markers, the COI and 16S ribosomal deoxyribonucleic acid (16S rDNA) markers for DNA barcoding of P. canaliculata and P. maculata. The COI and 16S rDNA sequences of 40 Pomacea specimens collected from six localities in Peninsular Malaysia were analyzed to assess their barcoding performance using phylogenetic methods and distance-based assessments. The results confirmed both markers were suitable for barcoding P. canaliculata and P. maculata. The phylogenies of the COI and 16S rDNA markers demonstrated species-specific monophyly and were largely congruent with the exception of one individual. The COI marker exhibited a larger barcoding gap (6.06–6.58%) than the 16S rDNA marker (1.54%); however, the magnitude of barcoding gap generated within the barcoding region of the 16S rDNA marker (12-fold) was bigger than the COI counterpart (approximately 9-fold). Both markers were generally successful in identifying P. canaliculata and P. maculata in the similarity-based DNA identifications. The COI + 16S rDNA concatenated dataset successfully recovered monophylies of P. canaliculata and P. maculata but concatenation did not improve individual datasets in distance-based analyses. Overall, although both markers were successful for the identification of apple snails, the COI molecular marker is a better barcoding marker and could be utilized in various population genetic studies of P. canaliculata and P. maculata.